Oral hygiene assessment of dental students using the Oral Rating Index (ORI) - Tirza Oktarina Setiabudi; Fajar Hamonangan Nasution (Dental Journal, 2022)
Background: Oral hygiene screening should be done on a regular basis, notably during the COVID-19 outbreak, during which lifestyle changes and government lockdown policies lower the oral hygiene level. The Oral Rating Index (ORI), established by Kawamura, is the suitable oral hygiene screening index during the COVID-19 pandemic. Dental students are supposed to be role models for the community by maintaining good dental hygiene. Purpose: To study the use of online oral hygiene screening using the ORI and to determine the oral hygiene of dentistry students at Trisakti University. Methods: This research is a cross-sectional descriptive observational study. A total of 100 preclinical dental students from Trisakti University took part in the study. Intraoral photos were taken and sent to the researcher via the internet. The ORI was used to evaluate the data. The reliability of the results was determined using a per cent agreement test and Cohen’s kappa coefficient. Results: The average oral hygiene score of dental students at Trisakti University was 0.58±0.88. The per cent agreement was 88%, and Cohen’s kappa coefficient was κ = 0.79, indicating excellent reliability. Conclusion: Based on their ORI score, it can be stated that dentistry students at Trisakti University have good oral hygiene and that online evaluation using the ORI is a useful tool for routine oral hygiene screening.